Postbiotic, anti-inflammatory, and immunomodulatory effects of aqueous microbial lysozyme in broiler chickens - Mustafa Bastamy; Ismail Raheel; Ahmed Elbestawy; Mohamed Diab; Enas Hammad; Lamiaa Elebeedy; Amal M. El-Barbary; Ghadeer M. Albadrani; Mohamed M. Abdel-Daim; Mervat A. Abdel-Latif; Ahmed Orabi (Animal Biotechnology)
Lysozymes, efficient alternative supplements to antibiotics, have several benefits in poultry production. In the present study, 120, one–day–old, Ross 308 broiler chickens of mixed sex, were allocated into 2 equal groups, lysozyme treated group (LTG) and lysozyme free group (LFG), to evaluate the efficacy of lysozyme (Lysonir®) usage via both drinking water (thrice) and spray (once). LTG had better (p = 0.042) FCR, and higher European production efficiency factor compared to LFG (p = 0.042). The intestinal integrity score of LTG was decreased (p = 0.242) compared to that of LFG; 0.2 vs. 0.7. Higher (p ≤ 0.001) intestinal Lactobacillus counts were detected in chickens of LTG. Decreased (p ≤ 0.001) IL-1β and CXCL8 values were reported in LTG. The cellular immune modulation showed higher (p ≤ 0.001) opsonic activity (MΦ and phagocytic index) in LTG vs. LFG at 25 and 35 days. Also, higher (p ≤ 0.001) local, IgA, and humoral, HI titers, for both Newcastle, and avian influenza H5 viruses were found in LTG compared to LFG. In conclusion, microbial lysozyme could improve feed efficiency, intestinal integrity, Lactobacillus counts, anti-inflammatory, and immune responses in broiler chickens.